A novelsearch algorithm for LSF VQ - Li, Jinyu (Proc. ICSLP, 2000)
Because classical fast vector quantization(VQ) algorithms can't be used in the LSF vector quantizers that use varying weighted Euclidean distance, a novel fast VQ search algorithm —CRVQCS (Constrained Range Vector Quantization based on Component Searching) is presented in this paper. The CRVQ-CS algorithm works well with the varying weighted Euclidean distance and yields the same result as full search VQ with reduced computational complexity does. Although the CRVQ-CS algorithm is proposed for VQ using varying weighted Euclidean distance measure, it is also suitable for VQ using simple Euclidean distance measure.